Produtividade do abacaxizeiro Jupi‟ e qualidade do abacaxi produzido na região litorânea sul capixaba - Bremenkamp, Cintia Aparecida (2011)
The objective of the present work was to study the pineapple production in the southern coastal region of Espírito Santo State, in Marataízes and Itapemirim. The specifics objectives were: developed a mathematical model to estimate the fruit weight of pin